Hydro-Catalytic Cracking of Biomass Tar Contamination in Syngas - Aris Warsita; Hasta Kuntara; Zainal Abidin (MBI, 2024)
This paper describes new tar removal argumentation method by adding water that enhances the steam reformation reactions and converts tar contamination in the gas into combustible gases. The hydro-catalytic tar removal method was experimentally evaluated in a microwave-heated reactor with toluene and naphthalene as tar models. The reactor was tested in a wide temperature range with flow residence time through the reactor in the range of 0.12-0.24s. Dolomite and nickel catalysts were tested at 700-900°С while Y-zeolite, ruthenium, and rhodium were tested at 500-700°С temperature ranges. Steam-to-carbon ratio (S/C) was tested in the range of 0.11-0.55. Tar removal efficiency of 98.88% was achieved with ruthenium catalyst at 700 °С cracking temperature and S/C ratio range of 0.32-0.33. The gas product from tar cracking was analysed using gas chromatography and it consisted mostly of H2, CH4 and some higher hydrocarbon gases.